Employee Performance from a Well-Being Perspective: The Mediating Role of Job Satisfaction - Toriqi Fajerin; Rahmat Agus Santoso; Abdul Kholid Achmad (Global Research Collaboration, 2026)
This study is motivated by the increasing complexity of public sector organizations in the era of digital transformation, which has intensified employee workloads and raised demands for organizational performance. Differences in employment status among Civil Servants (PNS), Government Employees with Work Agreements (PPPK/P3K), and honorary employees have created disparities in job security, compensation, and welfare, while employees are still expected to achieve similar performance targets. Therefore, this study aims to examine employee performance from a well-being perspective by analyzing the effect of Job Insecurity, Work Motivation, Organizational Commitment, and Compensation on Employee Performance through the mediating role of Job Satisfaction. This study employed a quantitative explanatory research design conducted at the Tourism, Creative Economy, Culture, and Youth and Sports Agency of Gresik Regency. Data were collected from 152 employees consisting of PNS, PPPK/P3K, and honorary employees using structured questionnaires. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings revealed that Job Insecurity negatively and significantly affected Job Satisfaction and Employee Performance, while Work Motivation, Organizational Commitment, and Compensation positively and significantly influenced Job Satisfaction and Employee Performance. Job Satisfaction was also proven to significantly mediate the relationship between the independent variables and Employee Performance. This study contributes theoretically by developing a comprehensive well-being-based employee performance model in the public sector and practically by providing strategic recommendations for improving employee welfare and sustainable organizational performance.